MENUMBUHKAN KREATIVITAS MAHASISWA MELALUI INTEGRASI TEKNOLOGI DALAM TASK BASED LANGUAGE TEACHING UNTUK MAHASISWA PENDIDIKAN BAHASA INGGRIS - Arik Susanti; Anis Trisusana; Ririn Pusparini; Esti Kurniasih (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2022)
Student creativity is needed in 21st century learning. When students have creative thinking skills, they can create new things that are innovative or creative. For this reason, this study aims to foster creative thinking skills for English students by using the Task-Based Language Teaching (TBLT)method that is integrated with technology in online learning and describes the results of student creativity. This study is a class study with participants are students majoring in English Education which amounts to 29. The research instrument is an observation and test sheet. Hasil research shows that the TBLT stage has been carried out well in learning by lecturers and students. This can be seen in the activities ofmahasiswa when they are able to develop English teaching materials, which starts from choosing KD and making a good GPA. In addition, analyze predetermined books and eventually they can create the development of the selected material using wakelet.com, as well as presenting synchronously (through zoom sessions and asynchronously (via wakalet). In addition, the results of the paired sample t-test analysis showed that the T-value was 0.000 and there was a significant increase in student creativity in the application of TBLT integrated with technology in the learning of Developing EFL Materials courses. It is concluded that to foster student creativity, methods are needed that can make the learning process more comfortable and interesting for students.